Shakespeare and religio mentis: A Study of Christian Hermetism in Four Plays - Nelson, Marion Jane, (Studies in Religion and the Arts ;, 2022)
Have you ever wondered why Cordelia has to die? Or how Alonso talks and walks about the isle while his body lies 'full fathom five' on the sea floor? Ever wondered why the monument to Shakespeare in the Church of the Holy Trinity in Stratford-upon-Avon names three pagans: Nestor, Socrates, and Virgil - king, philosopher, and poet? Or why Shakespeare is on Olympus, home of the Greek gods? This interdisciplinary study, the first to interpret the plays of Shakespeare in the light of the esoteric religious doctrines of the Corpus Hermeticum, holds answers to these and other puzzling questions.